2001
DOI: 10.1007/s00248-001-1022-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Algal Photosynthesis on Biofilm Bacterial Production and Associated Glucosidase and Xylosidase Activities

Abstract: Natural photosynthetic biofilms were incubated under light (100 mmol m-2 s-1) and dark conditions to elucidate the impact of photosynthesis on bacterial production, abundance, biovolume, biomass, and enzyme activities over 24 h. Use of organic carbon-free media limited carbon sources to algal photosynthesis and possibly the polysaccharides of the biofilm matrix. Bacterial production of biofilm communities was significantly higher in light incubations (p <0.001). The greatest differences in production rates bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 38 publications
3
48
1
2
Order By: Relevance
“…In biofilms, bacteria are in a close relationship with algae and rapidly utilize extracellular organic carbon (EOC) released from algal and cyanobacterial cells during active cell metabolism or following cell senescence (Espeland et al 2001). It has been shown that increased light intensities, to which cyanobacterial mats studied are exposed, stimulate extracellular enzyme activity (Espeland & Wetzel 2001a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In biofilms, bacteria are in a close relationship with algae and rapidly utilize extracellular organic carbon (EOC) released from algal and cyanobacterial cells during active cell metabolism or following cell senescence (Espeland et al 2001). It has been shown that increased light intensities, to which cyanobacterial mats studied are exposed, stimulate extracellular enzyme activity (Espeland & Wetzel 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Mats are an important component of northern Belizean marshes, constituting a major part of biomass and primary production coupled with both nitrogen fixation and production of large amounts of polysaccharide-rich extracellular polymeric substances (EPS). The production of EPS may be an important direct source of carbon for associated communities of heterotrophic bacteria (Bell et al 1983, Espeland et al 2001, while the nitrogen fixed in mats is utilized by non nitrogen-fixing bacteria and macrophytes (Rejmánková & Komárková 2000). Cyanobacterial mats also influence sediment formation in these systems in that large amounts of calcium carbonate are precipitated during photosynthesis forming marl deposits.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Peptidase activity was highest during periods of greatest algal biomass development in coarse substrata. This relationship may indicate the use of algal exudates (mainly peptidic molecules) by bacteria (Romaní et al, 2004), since bacterial enzyme production (especially peptidases) can be stimulated by active algal photosynthesis (Espeland et al, 2001). During this period, heterotrophic microbial activity may depend largely on the use of autochthonous sources.…”
Section: Discussionmentioning
confidence: 99%